Clean getaway - Stone, Nic (Crown Books for Young Readers, 2020)
"For the life of him, William "Scoob" Lamar can't seem to stay out of trouble--and now the run-ins at school have led to lockdown at home. So when G'ma, Scoob's favorite person on Earth, asks him to go on an impromptu road trip, he's in the RV faster than he can say FREEDOM. With G'ma's old maps and a strange pamphlet called the 'Travelers' Green Book' at their side, the pair takes off on a journey down G'ma's memory lane. But adventure quickly turns to uncertainty: G'ma keeps changing the license plate, dodging Scoob's questions, and refusing to check Dad's voice mails. And the farther they go, the more Scoob realizes that the world hasn't always been a welcoming place for kids like him, and things aren't always what they seem--G'ma included."--Jacket flap.